Thematic Hadits Studies: A Syar’i Study of Hadits on Marriage Witness - Idrus M. Said (Indonesian Journal of Multidisciplinary Science, 2023)
A valid marriage in Islamic law has a number of binding rules that must be fulfilled by the ummah, if the marriage is to be performed. These rules in addition to aiming to distinguish marriages performed before the arrival of Islam also distinguish the practice of marriage carried out by other religions. The study would like to discuss hadits on marriage witness. This study used library research. From the results of the study and reading of data sources, the researcher used and made the Literal Interpertation, namely legal discovery applied by explaining the legal texts of marriage witnesses in hadith related to marriage witness law. It means that the witness of marriage that becomes law already has a legal text despite it being unclear or incomplete. The study found out that the hadith about marriage witnesses, as Imam Tirmidzi mentions, that the narration is not judged marfu', except by Abdul A'la but he also judged mauquf to be more correct and did not cause this hadith to be flawed, because Abdul A'la was a tsiqah so that his marfu judgment and its additions were acceptable.